The Effects of Work Climate, Discipline, and Professional Competence on Elementary School Teachers’ Performance - Puspitawati; Tin Agustina K; Dany Moenindyah H (Al-Qalam Institue, 2026)
This study aims to examine the influence of work climate, discipline, and professional competence on teacher performance, both partially and simultaneously. A quantitative research design was employed using a survey approach, and data were analyzed through multiple linear regression. The population consisted of all teachers in the 2025–2026 academic year, with 42 respondents selected using a saturated sampling technique. The findings reveal that partially, work climate does not have a significant effect on teacher performance. Discipline shows a significant but negative effect, indicating an inverse relationship. In contrast, professional competence has a positive and significant effect on teacher performance. Simultaneously, work climate, discipline, and professional competence collectively have a significant influence on teacher performance. These findings imply that strengthening teachers’ professional competence should be prioritized to enhance performance, while discipline policies require careful evaluation to avoid unintended negative impacts. The study contributes to the development of human resource management strategies in educational institutions.